Konsep Blue Economy di Daerah Pesisir Kota Samarinda dengan Pendekatan Penta Helix - Luturmas, Fabiola; Maulita, Maulita; Syam, Herdi (Saintara : Jurnal Ilmiah Ilmu-Ilmu Maritim, 2024)
Blue economy is a concept of marine-oriented development, not only exploiting resources but also maintaining and protecting ecosystems. This research aims to analyze the impact of economic activities carried out and the involvement of stakeholders seen with the Penta Helix approach. The research method used in this research is qualitative. The results of this study found that the implementation of the Blue economy in Samarinda City, based on the Penta Helix approach, has been carried out by academics, especially in maritime-based schools, then from the business side, business actors in Samarinda City are trying to protect the environment by trying to produce environmentally friendly waste. From the Community side, in Samarinda City there is a Fishermen community as a place and place to devote aspirations to develop the activities of fishermen, then the Samarinda City Government plays an active role in providing policies that support Fishermen in Samarinda City and the last is the Media, as a means of socializing the blue economy and a source of information to promote the application of the blue economy.